A Survey of Using Internet of Things to Enhance Zero Energy Buildings (Texas Journal of Multidisciplinary Studies, 2021)
With the development of the Internet of Things (IoT) technology, people have higher requirements for quality of life, and they have put forward higher requirements for visualization and intelligence for various environmental indicators of the house. Buildings are one of the largest energy consumers. Renewable energies, in addition to electricity networks, can be employed to meet the energy demands of buildings. Building energy consumption could also be managed using intelligent systems such as the Internet of Things (IoT) and wireless sensor technologies. Luckily, combining renewable energy sources with these sophisticated technologies allows for the construction of nearly zero-energy structures. Therefore, in this research article, we will highlight the Internet of Things (IoT) network that interconnected computing devices and technologies with the goal of enhancing efficiency in energy use in both residential and commercial buildings. To properly appreciate the application of IoT to increase energy efficiency in buildings, a thorough review of a plethora of empirical surveys and research will conduct. A modern overview of the current research also looks into how these technologies might be improved furthermore required solutions should be provided. The majority of the research we looked at focused on the applicability of various components of IoT to a given application.